ENVIRONMENTAL POLLUTANTS AND THEIR IMPACT ON HUMAN HEALTHc (Scientific journal of the Fergana State University, 2024)
Numerous environmental pollutants contribute significantly to human disease by influencing climate change and public and individual health, leading to increased mortality and morbidity. Due to the lack of information on pollution exposure in less developed countries with inadequate waste management, higher poverty rates, and limited adoption of new technologies, the relationship between pollutants and health outcomes requires further study. A similar situation is observed in many developed countries, where solutions are discovered only after the harm has already been done and the need for protective measures has ceased. There is a need to better understand the relationship between environmental toxins and health due to difficulties in quantifying exposure levels and lack of systematic monitoring. Various pollutants cause both chronic and acute diseases.Additionally, research becomes challenging when disease problems are observed after long-term exposure. The purpose of this review is to discuss the current understanding of the relationship between environmental toxins and human health with the goal of addressing this knowledge gap.